PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATERI PENGELOLAAN KATA SANDI DAN AUTENTIKASI DUA LANGKAH PADA KELAS X SMAN 7 MALANG - Kalifatullah, M. Ajie; Prasetya, Didik Dwi; Setiawan, Ahmad Yusuf; Anwar, Khoirul; Wahfi, Muhammad Fikri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study highlights the importance of digital literacy and awareness of cybersecurity in 21st-century education, particularly at the high school level. It aims to examine the effect of the Problem-Based Learning (PBL) model on students' learning outcomes regarding password management and two-factor authentication. The research employs a quasi-experimental method with a one-group pretest-posttest design, involving 10th-grade students at SMAN 7 Malang as the subjects. The research instruments include learning outcome tests and student activity observation sheets. The results indicate that the application of PBL significantly impacts students' learning outcomes, as evidenced by the statistically significant difference between pretest and posttest scores. In addition to promoting active student engagement, this model proves effective in fostering conceptual understanding and critical awareness of digital security issues. These findings suggest that prospective teachers possess strong pedagogical and digital literacy competencies and are capable of designing innovative, contextual learning. Consequently, this research reflects the leadership of future educators in providing solutions for learning based on the needs of the times and supporting the achievement of Indonesia’s Vision 2045.